Penerapan Data Mining Dalam Menganalisa Pola Peminjaman Buku di Perpustakaan SMP Negeri 2 Beringin Satu Atap Menggunakan Algoritma Apriori - Kristiani Romili Sitanggang; Penda Sudarto Hasugian (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2018)
The library is a facility that provides information, sources of knowledge, and tools for learning. All this time,in the library of the One Roof One-Banyan One-Roof Junior Secondary School, in book lending transactions,they are only stored without any further data processing. In fact, the large amount of lending transaction datacan be used to find out the association rules between two or more books. To facilitate the process of borrowingbooks in a library, especially in terms of finding books to be borrowed, Apriori algorithm with the associationrules (association rules) so that information can be extracted about what books are often borrowed and knowthe pattern of the relationship between books that have been borrowed together so that later can be used tomake the preparation of books in accordance with the existing book lending patterns so can facilitate libraryvisitors in the process of finding books